2021
DOI: 10.22490/24629448.5294
|View full text |Cite
|
Sign up to set email alerts
|

Potencial antimicrobiano de extractos de plantas medicinales y sus mezclas frente a bacterias asociadas con conjuntivitis

Abstract: Introducción. La conjuntivitis bacteriana es una de las infecciones oculares con mayor tasa de consulta oftálmica, siendo el género Staphylococcus el agente etiológico que presenta mayor resistencia a los antibióticos. Objetivo. Determinar el potencial antimicrobiano de extractos de plantas medicinales y sus mezclas frente a bacterias asociadas con conjuntivitis. Métodos. A partir de plantas como Belladona, Caléndula, Albahaca, Achiote y Romerillo se prepararon los extractos etanólicos y se evaluó su potencial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…8 A synergistic or additive effect between plant extract and antibiotics has already been demonstrated in the context of bacterial conjunctivitis. 11 When considering chamomile-containing preparations for the ear and eye, factors such as the concentration of active compounds, the formulation of the preparation, and the specific pathogens commonly associated with ear and eye infections need to be addressed. Different extracts from chamomile flowers have differential antibacterial effects on specific microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 A synergistic or additive effect between plant extract and antibiotics has already been demonstrated in the context of bacterial conjunctivitis. 11 When considering chamomile-containing preparations for the ear and eye, factors such as the concentration of active compounds, the formulation of the preparation, and the specific pathogens commonly associated with ear and eye infections need to be addressed. Different extracts from chamomile flowers have differential antibacterial effects on specific microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, such differences can also be affected by the species of Matricaria and the part of the plant from where the extract is obtained. 11 This is important as sometimes the plant available in the market may be adulterated and substituted by close relatives of chamomile. 7 Although this study provides valuable insights into the antimicrobial activity of over-the-counter chamomile-containing ear and eye drops, these were exclusively tested against planktonically grown organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial effect of polyphenolic extracts present in ananas comosus On the other hand, the microbiological analysis carried out showed a variability in the inhibition halos which is significant because according to (33) previous results of inhibition halos of 28 and 18 mm have been reported, as reported by ( 34) and ( 35), as well as in the research carried out by (36), establishes that bacteria tend to produce resistance mechanisms against antimicrobials, which in the case of Staphylococcus aureus are related to the activation of cell wall synthesis, with the production of proteins, which once these resistance mechanisms are activated, create a greater firmness against the applied agent. It was also observed that treatment three corresponds to the highest concentration of pineapple crown extract, being the most representative in terms of inhibitory capacity, which indicates a gradual inhibition capacity, with a smaller inhibition halo being observed at lower concentrations of the extract.…”
Section: Microbiological Analysismentioning
confidence: 99%